Uterine Weight as a Modifier of Black/White Racial Disparities in Minimally Invasive Hysterectomy Among Veterans with Fibroids in the Veterans Health Administration (Mary Ann Liebert, 2022)
Introduction: Uterine fibroids are the most common indication for hysterectomy. Minimally invasive hysterectomy (MIH) confers lower risk of complications and shorter recovery than open surgical procedures; however, it is more challenging to perform with larger fibroids. There are racialized differences in fibroid size and MIH rates. We examined the role of uterine size in black-white differences in MIH among Veterans in the Department of Veterans Affairs (VA). Methods: Using VA clinical and administrative data, we conducted a cross-sectional study among black and white Veterans with fibroids who underwent hysterectomy between 2012 and 2014. We abstracted postoperative uterine weight from pathology reports as a proxy for uterine size. We used a generalized linear model to estimate the association between race and MIH and tested an interaction between race and postoperative uterine weight (?250?g vs. >250?g). We estimated adjusted marginal effects for racial differences in MIH by postoperative uterine weight. Results: The sample included 732 Veterans (60% black, 40% white). Postoperative uterine weight modified the association of race and MIH (p for interaction=0.05). Black Veterans with postoperative uterine weight ?250?g had a nearly 12-percentage point decrease in MIH compared to white Veterans (95% CI ?23.1 to ?0.5), with no difference by race among those with postoperative uterine weight >250?g. Discussion: The racial disparity among Veterans with small fibroids who should be candidates for MIH underscores the role of other determinants beyond uterine size. To eliminate disparities in MIH, research focused on experiences of black Veterans, including pathways to treatment and provider-patient interactions, is needed.